Patterning of a Cohesionless Granular Layer Under Pure Shear - Melo-Hurtado, F (American Physical Society, 2018)
The response of a thin layer of granular material to an external pure shear imposed at its base is investigated. The experiments show that, even for noncohesive materials, the resulting deformation of the material is inhomogeneous. Indeed, a novel smooth pattern, consisting of a periodic modulation of the shear deformation of the free surface, is revealed by an image-correlation technique. These observations are in contrast with the previous observation of the fracture pattern in cohesive granular materials subjected to stretching. For cohesive materials, the instability is due to the weakening of the material which results from the rupture of capillary bridges that bond the grains to one another. For noncohesive materials, the rupture of the capillary bridges cannot be invoked anymore. We show that the instability results from the decrease of friction on shearing. PACS: 89.75.Kd: Pattern formation in complex systems; 83.60.Uv: Rheology: fracture; 45.70.Qj: Pattern formation in granular matter. © 2018 American Physical Society.